2016
DOI: 10.1037/hea0000333
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of change in diet and activity in the Make Better Choices 1 trial.

Abstract: Objective The Make Better Choices 1 trial demonstrated that participants with unhealthy diet and activity behaviors who were randomized to increase fruits/vegetables and decrease sedentary leisure achieved greater diet and activity improvement than those randomized to change other pairs of eating and activity behaviors. Participants randomized to decrease saturated fat and increase physical activity achieved the least diet-activity improvement. This study examined which psychological mechanisms mediated the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 41 publications
3
16
0
Order By: Relevance
“…Fruit and vegetable intake and sedentary leisure showed the largest improvements in this study, as they had in our prior MBC1 study. Notably, in the MBC1 study, improvements in these two behaviors were also unique in being accompanied by increased self-efficacy, suggesting that changing them is both feasible and empowering [ 60 ]. Although intervention benefits persisted through nine months, longer duration follow-up remains needed.…”
Section: Discussionmentioning
confidence: 99%
“…Fruit and vegetable intake and sedentary leisure showed the largest improvements in this study, as they had in our prior MBC1 study. Notably, in the MBC1 study, improvements in these two behaviors were also unique in being accompanied by increased self-efficacy, suggesting that changing them is both feasible and empowering [ 60 ]. Although intervention benefits persisted through nine months, longer duration follow-up remains needed.…”
Section: Discussionmentioning
confidence: 99%
“…Both patients and clinicians need to be committed to mHealth interventions in order to achieve long-term impact. In a recent mHealth trial on diet and exercise behaviour in healthy volunteers with an increased risk of atherosclerosis, the dropout rate was as high as 20 % [ 19 ]. Therefore, it is important to seek the right balance between time-consuming data collection and dropout.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in protein intake among participants was also consistent with the findings of other studies using coaching. These other studies, however, successfully used coaching to help participants improve food choices to reduce risks of conditions such as diabetes, heart disease, and obesity (15)(16)(17)(18). In systematic literature reviews, coaching has been shown to significantly impact behavior change including dietary modifications (15,17).…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining the effects of protein on muscle have typically provided participants with supplements (whey, casein-or soy-based powders or amino acids) versus allowing participants to self-select protein-rich foods (10)(11)(12)(13)(14). Coaching has been used successfully to help adults change dietary behaviors, primarily improving food choices to reduce disease risks associated with type 2 diabetes, heart disease, and obesity (15)(16)(17)(18). Missing from the literature, and which will be fulfilled from this study, is the use of coaching for the purpose of helping adults to improve their protein intake and the use of protein-rich foods (not supplements) to improve muscle strength and physical function.…”
Section: Introductionmentioning
confidence: 99%